Transformasi Pendidikan Karakter Berbasis Akhlak : Analisis Hadits Arbain An-Nawawi - Muhammad Akmansyah; Elsa Al Khansa; Herlina Herlina (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
Character education is an essential aspect of Islam in shaping individuals with noble morals. Hadith, especially those compiled in Arbain an-Nawawi, contains many moral values that can be applied in daily life. This study aims to identify moral values in Arbain an-Nawawi, analyze how to implement them in education, and examine the challenges and solutions in their application. This research uses content analysis to examine the hadiths in Arbain an-Nawawi.The findings reveal that the moral values in these hadiths fall into three main categories: (1) Morals toward Allah, such as sincerity (ikhlas) and trust in God (tawakal); (2) Morals toward others, such as honesty and compassion; and (3) Morals toward oneself, such as self-reflection and anger management. These values can be taught through exemplary behavior, habituation, self-reflection, and storytelling. However, there are several challenges in implementing hadith-based character education, such as a lack of understanding among educators regarding hadith, an education system that prioritizes academics over character development, and the influence of modern culture and technology. To address these challenges, teacher training, the strengthening of character-based curricula, and the use of technology as a learning medium are necessary. This study is expected to provide insights for the educational sector in strengthening students’ character based on Islamic teachings.